2001
DOI: 10.1007/bf03343856
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic hypophysitis: Its expanding features

Abstract: Lymphocytic hypophysitis is classically defined as an inflammatory disorder confined to adenohypophysis. However, it has recently been indicated that infundibuloneurohypophysitis underlies some subsets of central diabetes insipidus (DI). Therefore, lymphocytic hypophysitis can be considered a syndrome including disorders of both the anterior pituitary (lymphocytic adenohypophysitis) and the posterior pituitary (lymphocytic infundibuloneurohypophysitis). We describe a 77-yr-old woman with lymphocytic hypophysit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 95%
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 95%
“…There have been some recent reports of patients presenting with both anterior and poste-rior pituitary dysfunction (2, 7). Therefore, it may be appropriate to consider lymphocytic hypophysitis as a syndrome involving both the anterior and posterior pituitary (4). Differential diagnosis to differentiate lymphocytic hypophysitis from other pituitary diseases includes pituitary adenoma, sarcoidosis, tuberculosis, and granulomatous hypophysitis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytic hypophysitis is considered a syndrome including disorders of the anterior pituitary (lymphocytic adenohypophysitis), and the posterior pituitary (lymphocytic infundibuloneurohypophysitis). The latter usually presents with central diabetes insipidus (4). Although central diabetes insipidus may be idiopathic or secondary to a disturbance of the hypothalamic-neurohypophysial system including trauma, infection, tumors or other lesions, lymphocytic infundibuloneurohypophysitis has been suggested as the underlying cause in some cases previously labeled "idiopathic diabetes insipidus" (5).…”
Section: Introductionmentioning
confidence: 99%
“…phocytic hypophysitis is classified as follows: LAH, LINH, and panhypophysitis [14]. It may be appropriate to consider lymphocytic hypophysitis as a syndrome involving both the anterior and posterior pituitary [13]. The most unique and prominent MRI features are the pituitary stalk thickening and marked enlargement of the pituitary gland with homogeneous contrast enhancement.…”
Section: Case Reportmentioning
confidence: 99%